The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.3928/0191-3913-20060301-14
|View full text |Cite
|
Sign up to set email alerts
|

Pseudallescheria boydii Keratitis

Abstract: Abstract. We describe a patient with Pseudallescheria boydii keratitis. The treatment of mycotic keratitis remains difficult. This case demonstrates that identification and susceptibility testing should be rapidly performed. In cases of indolent keratitis, the possibility of fungal infection should be kept in mind. J Pediatr Ophthalmol Strabismus 2006;43:114-115.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…There are other reports of successful treatment using topical voriconazole, miconazole, nystatin, and amphotericin B. 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 This organism has septate, thin-walled, branching hyphae and an angioinvasive tendency. 14 There is not any report of confocal scanning of this type of fungal keratitis in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…There are other reports of successful treatment using topical voriconazole, miconazole, nystatin, and amphotericin B. 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 This organism has septate, thin-walled, branching hyphae and an angioinvasive tendency. 14 There is not any report of confocal scanning of this type of fungal keratitis in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Internal transcribed spacer (ITS) gene sequencing establishes a rapid and prompt diagnosis of fungal keratitis in refractory cases[ 21 ] and has been described in Pythium along with other non-sporulating molds. [ 22 23 24 25 26 27 28 29 30 31 32 33 ]…”
Section: Diagnosismentioning
confidence: 99%
“…Several new pathogenic fungi causing keratitis, with varying or suboptimal susceptibility to antifungal therapy, are emerging [ Table 2 ]. [ 23 24 25 26 27 28 29 30 31 32 33 34 35 45 46 47 48 49 50 51 52 ] Knowledge of the sensitivity profile of antifungals by antifungal susceptibility test (AFST) against various species helps in initiating appropriate treatment and improving the outcome. A recent study from South America reported A. fumigatus isolate from post-traumatic keratitis in a 27-year-old male worker carrying the substitution G54E at Cyp51Ap associated with itraconazole resistance, highlighting the possibility of mutation-induced resistance to common antifungal therapy.…”
Section: Emerging New Pathogenic Microbesmentioning
confidence: 99%